Comparison of classic constraint-induced movement therapy and its modified form on upper extremity motor functions and psychosocial impact in hemiplegic cerebral pals - Afzal, Mamoona Tasleem; Amjad, Imran; Ghous, Misbah (Journal of the Pakistan Medical Association, 2022)
A prospective randomised control trial (RCT) was conducted in National Institute of Rehabilitation Medicine (NIRM), Islamabad, on 40 children with hemiplegic cerebral palsy (HCP). Children between the ages of four and12 years with ipsilateral, bilateral or severely asymmetrical impairments who had wrist extension (20°) and fingers flexion (10°) were included. The outcomes tools, Box and Block Test, Quality of Upper Extremity Skill Test, CP (Quality of Life) and Kid screen were used at baseline, mid- and post- treatment assessment. Both the treatment approaches (CCIMT AND MCIMT) equally improved upper limb motor functions and psychosocial life of the children with HCP. On Quest tool, results of dissociated movement were significant (p=0.021) and on CPQOL tool two domains (participation & physical health and family health) showed significant difference (p=0.042, p=0.025). But no significant difference was noted regarding other domains of the tools. The study concluded that both the treatment approaches (CCIMT AND MCIMT) are effective in enhancing the upper limb motor functions and psychosocial life of children with HCP. Keywords: Constraint-induced movement therapy, Cerebral palsy, upper extremity.